Accommodation payment plans in residential aged care: The impact of consumer choice. (7th August 2019) - Abiona, Olukorede; Yu, Serena; Woods, Mike; van Gool, Kees
Abstract: Objective: To examine changes in accommodation payments to residential aged care facilities following the introduction of consumer choice reforms in 2014. These reforms have allowed residents to choose between making lump sum refundable deposits and/or rental‐style payments. Methods: Quantitative analysis was undertaken for facility‐level quarterly data of 136 separate facilities, which were operated by six providers over the period under study. Results: While the total pool of payments has grown strongly, consumers have increasingly favoured rental‐style payments over lump sum refundable deposits. Conclusion: Consumer choice has changed the landscape of accommodation payment receipts in the provision of residential aged care services. Greater understanding is needed on how consumer preferences impact on the financial risk borne by providers and their ability to invest in future capacity.